Avtomatično računalniško merjenje premera retinalnih krvnih žil s prilagoditveno metodo sledenja v povezavi s krvnim tlakom - Ikica, Andrej (Zdravniški vestnik, 2007)
Methods 295 patients with increased blood pressure were analyzed. All arterioles and venules located in the area between one half and one disc diameter from the optic disc margin were measured with the computer based program. These measurements were combined to provide the average diameters of retinal arterioles and venules and the association with blood pressure was analyzed. The arteriole-to-venule ratio (AVR) was also calculated. Results Theaverage arteriolar diameter of patients who had hypertension from 5 to 15 years was 89.311 micro m. Patients with hypertension for more than 15 years they had value of 79.276 micro m. Average venular diameters were very similar in both groups (103.319 micro m vs. 101.392 micro m). We noticed differences in average arteriolar diameter between control group and hypertonic patients who had hypertension for more than 15 years (92.083 micro m vs. 79.276 micro m). Venular differences were minimal. The average of retinal venules in control group was 106.029 micro m, in patients with hypertension for more than15 years it was 101.392 micro m. Conclusions Using a computer-assisted method to measure retinal vessel diameter we found out that the diameter of retinal arterioles narrowed with blood pressure level. Our findings demonstrate a relation between presence and severity of hypertension and retinal diameter. Diameter of retinal venules hardly changed. Such relationship was similar with men and women. Fully automated system for analyzing retinal vessels is simple to use, quick and reliable.
Keywords: arterije; Arteriole; Arterioles; Diagnosis; Diagnosis, Computer-Assisted; Diagnostika z računalnikom; Fundus Oculi; Hipertenzija; Hypertension; krvni tlak; merjenje; Mrežnična arterija, okluzija; Mrežnična vena, okluzija; Očesno ozadje; oči; Oftalmoskopija; Ophthalmoscopy; Pupil; Pupila; Retinal Artery Occlusion; Retinal Vein Occlusion; Venule; Venules